Supporting the spatial allocation of management practices to improve ecosystem services – An opportunity map approach for agricultural landscapes - Irina Heiß; Friederike Stegmann; Matteo Wolf; Martin Volk; Andrea Kaim (Ecological Indicators)
Ecosystem services (ES) − the benefits people obtain from ecosystems − are affected by agricultural management. Often, they are degraded because of practices that solely aim at maximizing yield regardless of their impact on other ES, such as water regulation or habitat provision for biodiversity. Therefore, the spatial targeting of suitable agri-environmental schemes (subsidized by the Common Agricultural Policy of the EU) is needed to address degraded ES in specific areas. To study the interrelations and spatial patterns of ES and agricultural management, there is no compromise between time- and data-intense process-based models and rather simple ES maps based on land use types and single proxies. Therefore, we propose an opportunity map approach, which enables both regional overview and field-specific evaluation on where ES can be improved through agricultural management changes. For this purpose, we developed evaluation criteria and scores for site conditions, management data from 2022 and other spatial environmental parameters based on literature research and expert interviews. These evaluation criteria were assigned scores indicating the opportunity to improve the ES “provision of clean water”, “habitat provision”, “carbon sequestration” and “water regulation” (approximated by drought protection) through altered management. Individual criteria were developed for each ES and weights for the ES criteria resulted from expert interviews using the Analytic Hierarchy Process. Except for the management data, all spatial data sets were publicly available. The study region of Northwest Saxony, Germany – an intensively cultivated agricultural area – showed an overall high opportunity to improve ES through management changes. The highest opportunities were identified for the ES “provision of clean water” and “habitat provision”.This novel approach is fast, reproducible and can be transferred to and adapted for other German regions and ES. Therefore, it helps decision-makers to spatially target management suggestions and to support information campaigns or subsidy schemes for management practices with positive impacts on ES.